Effects of Different Base Fertilizers on Water Use Efficiency and Growth of Maize During Growth Period - Wang, Zhenchao; Wang, Keqin; Liu, Xinyi; Zhu, Wanjing; Deng, Xiangyin; Zhao, Yangyi (Agronomy (Basel), 2025)
This study hypothesized that different base fertilizer application has different effects on improving the efficiency of maize water utilization and promoting maize growth. Utilizing field positioning sloping farmland micro-zone experiments, six distinct types of base fertilizers were designed: a control group without fertilization (CK), chemical fertilizer alone (T1), a mixture of local farmyard manure (40% pine needles and 60% livestock manure, T2), a 50% reduction in chemical fertilizer combined with farmyard manure (T3), the incorporation of crushed straw through deep plowing (T4), and the fermentation of crushed straw mixed with urea before field application (T5). The results indicate that, compared to the CK treatment, the T3 and T5 treatments significantly enhanced soil moisture content, with increases ranging from 4.06% to 18.67% during the normal year (2023) and the drought year (2024), respectively. Additionally, the water utilization efficiency of maize was improved significantly, with values of 35.38% and 41.54%, and the yield increased by 12.30% to 25.92%. The maize yields under T3 and T5 treatments reached 12.19 and 13.31t/ha, respectively. Therefore, we propose that crushing straw and incorporating urea and water for fermentation as a base fertilizer in maize fields can ensure efficient water use in this region, leading to higher yields.